2021
DOI: 10.1088/1475-7516/2021/02/004
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of dark matter - electron scattering on the galactic dark matter velocity distribution

Abstract: The rate of dark matter-electron scattering depends on the underlying velocity distribution of the dark matter halo. Importantly, dark matter-electron scattering is particularly sensitive to the high-velocity tail, which differs significantly amongst the various dark matter halo models. In this work, we summarize the leading halo models and discuss the various parameters which enter them. We recommend updated values for these parameters based on recent studies and measurements. Furthermore, we quantify the dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 140 publications
0
23
0
Order By: Relevance
“…Other authors have suggested updates to the SHM that differ from those presented here, including Refs. [43,44] among others. We recommend to report results with respect to the nominal halo model, which will give a common point of comparison, while knowledge of the dark matter halo continues to improve, unless new measurements significantly alter the expected spectra, particularly at high masses.…”
Section: Experimenter Bias Mitigationmentioning
confidence: 99%
“…Other authors have suggested updates to the SHM that differ from those presented here, including Refs. [43,44] among others. We recommend to report results with respect to the nominal halo model, which will give a common point of comparison, while knowledge of the dark matter halo continues to improve, unless new measurements significantly alter the expected spectra, particularly at high masses.…”
Section: Experimenter Bias Mitigationmentioning
confidence: 99%
“…They may also provide important clues to break the degeneracy between the interacting dark matter effects and the warm dark matter effects. Finally, future prospects in direct detection, indirect detection, and collider searches, in addition to an increasingly more accurate understanding of the local density and velocity distributions of dark matter, which plays a vital role in direct detection efforts [143][144][145][146][147][148][149][150][151][152], could shed light on the mystery of the nature and interactions of dark matter. parameter space for dark matter-protons interaction and n = 0 (upper), n = −2 (middle), and n = −4 (lower), assuming f χ = 100% of dark matter interacts with protons.…”
Section: Discussionmentioning
confidence: 99%
“…Other mergers may leave more diffuse remnants, like the radially-anisotropic stellar substructure observed by Gaia (dubbed the "Gaia Enceladus" or "Gaia sausage"), implying corresponding DM substructure that may be ∼ 20% of the local DM density [29,35]. It is an open question to what extent the smooth component of the DM distribution may be correlated with stars, but the consequences for light DM phenomenology are largely driven by the quasi-Maxwellian bulk of the distribution, though important effects at experimental thresholds do arise from the high-velocity tail [36].…”
Section: A Kinematicsmentioning
confidence: 99%